DECELERATING PRESHOCK SEISMIC DEFORMATION IN FAULT REGIONS DURING CRITICAL PERIODS - Papazachos, C.; Scordilis, E.; Karakaisis, G.; Papazachos, B. (Bulletin of the Geological Society of Greece, 2004)
We examine the behavior of the intermediate magnitude preshock activity in the fault region of a mainshock during the critical period, that is, in the period when accelerating seismic activity is observed in a broader region (critical region). For this purpose, data concerning 10 recent strong mainshocks (M=6.6-8.3) occurred since 1981 in Greece, Anatolia, Japan and California are used. It is observed that during the critical preshock period, decelerating seismic crustal deformation (Benioff strain) is observed in the fault region (within the fault zone and its close vicinity), whereas accelerating deformation is observed in the broader (critical) region. The dimension of the fault region where decelerating deformation is observed scales positively with the mainshock magnitude and negatively with the mean seismicity rate of this region. The duration of this decelerating deformation scales also negatively with the mean seismicity rate. The physical explanation and importance of these results for earthquake prediction are discussed